The Essentials of Clinical Trial Management: Addressing Needs for Successful Outcomes - Gunjan Kumar; Aparna Mukherjee (Journal of Medical Evidence)
Clinical trials are essential for evaluating the safety and efficacy of new medical interventions, ensuring evidence-based advancements in healthcare. They play a critical role in improving patient outcomes and guiding regulatory approvals for new treatments. India has emerged as a key player in clinical trials, owing to its skilled manpower, state-of-art infrastructure and robust regulatory framework. The manuscript has been written with the objectives of summarising the key imperatives of clinical trial administration including strategic planning, focusing on the development of protocol, appropriate study designs and the establishment of SMART objectives. It further emphasises regulatory compliance, ethics and the selection of study sites based on epidemiological and infrastructural factors. The role of data management, especially electronic data capture, and the necessity of robust monitoring, including risk-based approaches, are then highlighted. The document also addresses common challenges such as patient recruitment, retention, budgeting and site coordination, and proposes solutions, such as leveraging technology and ensuring ethical standards. Finally, it examines the complexities of multi-centric clinical trials, offering strategies for overcoming these hurdles.